Beliefs of East Borneo EFL Teachers Concerning World Englishes - Tahir, Herlina; Susilo, Susilo; Ping, Maria Teodora (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Many researchers have examined students' perceptions of World English. However, little research has been conducted on what teachers in East Borneo think about this topic. Therefore, it is important to find out whether EFL East Borneo teachers are able to teach and introduce the concept of International English. This research seeks to examine East Borneo EFL instructors' beliefs of World Englishes and their application of these varieties in the classroom. The subjects were thirty EFL English instructors in Balikpapan, Samarinda, Kutai Kartanegara, Bontang, Kutai Timur, PPU, and Berau District of East Borneo Province. The method used to gather data was a questionnaire with Likert scales and open-ended questions on teachers' attitudes and practices towards World Englishes. Percentage, mean, and standard deviation were used to examine the data (S.D). The study's results found that East Borneo EFL teachers executed their ideas by teaching students to communicate like native speakers. They generally expose students to standard English in terms of accents, grammar, vocabulary, idioms, and the use of a standard English dictionary. On the other hand, they followed the World Englishes paradigm in educating culture, choosing and using books and resources with varying levels of English.